2009
DOI: 10.1159/000222670
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Reduce Glial Fibrillary Acidic Protein Expression in Response to Spinal Cord Injury in a Fetal Rat Model of Dysraphism

Abstract: Background: Exposure of the spinal cord in myelomeningocele (MM) throughout gestation increases spinal injury. Astrocyte activation evidenced by glial fibrillary acidic proteins (GFAP) indicates the extent of injury. Corticosteroids modulate GFAP synthesis, but their effect in MM is unclear. The purpose of this study was to evaluate the GFAP expression in a fetal rat model of dysraphism and the effect of corticosteroid treatment on this marker and on clinical neurological disabilities. Methods: Dysraphism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…In this RA-induced rat model, the most common neuropathological feature described was the presence of reactive astroglia in spinal cords of fetuses with spina bifida exposed to the amniotic fluid. Astrogliosis has been described before in this model 8 and other spina bifida animal models 20 , 21 , but in our model we detected earlier activation at E15 in the exposed spinal cords from spina bifida fetuses.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this RA-induced rat model, the most common neuropathological feature described was the presence of reactive astroglia in spinal cords of fetuses with spina bifida exposed to the amniotic fluid. Astrogliosis has been described before in this model 8 and other spina bifida animal models 20 , 21 , but in our model we detected earlier activation at E15 in the exposed spinal cords from spina bifida fetuses.…”
Section: Discussionsupporting
confidence: 59%
“…Astrogliosis has been previously described in animal models of spina bifida 18 , 20 at E16.5-E18. Normal astrogenesis in rat fetuses starts at E18 and continues after birth until post-natal day7 26 .…”
Section: Discussionmentioning
confidence: 86%
“…The establishment and improvement of disease animal models are important for revealing the pathogenesis of human spina bifida, and play key roles in testing novel interventions (Smith et al, 1978;Duru et al, 2001;Danzer et al, 2005). Recent years, researchers have explored the effects of some risk factors by using these animal models (Zhao et al, 2008;Qin et al, 2016), and take further measures such as gene and cell therapy strategies to intervene to reduce the occurrence of perinatal birth defects (Melo-Filho et al, 2009;Turner et al, 2013;Wei et al, 2020a). It is indicated that genetic therapy may become a novel strategy for treating birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Weber Guimarães Barreto et al [57] found that there is a high incidence of Chiari malformation in this rat model [57]. The same group (2009) evaluated the effect of steroid therapy on neurological disabilities and reported significant clinical improvement after treatment [58].…”
Section: The Surgical Modelmentioning
confidence: 84%
“…Gillman et al [51] 1948 Description of the trypan blue model Heffez et al [53] 1990 Creation of the surgical model and proposition of the "two-hit" hypothesis Heffez et al [54] 1993 Intrauterine treatment of the surgical model Drewek et al [55] 1997 Amniotic fluid becomes toxic at 34 weeks of gestation Correia-Pinto et al [56] 2002 Effect of human meconium on the exposed spinal cord Danzer et al [12] 2005 Description of the all-trans retinoic acid model Melo-Filho et al [58] 2009 Effect of corticosteroid treatment on neurological disabilities Pennington et al [64] 2013 Amniotic fluid profile correlates with type and size of neural tube defect Dionigi et al [66] 2015 MMC coverage induced by stem cells Zieba et al [70] 2017 Examined the cellular content of amniotic fluid Kajiwara et al [72] 2017 Used artificial skin in fetal coverage of MMC Tang et al [73] 2017 Analyzed chitosan-gelatin membrane patch for the fetal treatment of MMC Farrelly et al [74] 2019 Studied the amniotic injection of alginate with fibroblast growth factors Abe et al [75] 2019 Used injection of human amniotic fluid stem cells…”
Section: Authors Year Contributionmentioning
confidence: 99%